Halo Mass-observable Proxy Scaling Relations and Their Dependencies on Galaxy and Group Properties - Zhang, Ziwen; Wang, Huiyuan; Luo, Wentao; Mo, Houjun; Zhang, Jun; Yang, Xiaohu; Li, Hao; Li, Qinxun (The Astrophysical journal, 2024)
Based on the DECaLS shear catalog, we study the scaling relations between halo mass ( M h ) and various proxies for Sloan Digital Sky Survey central galaxies, including stellar mass ( M * ), stellar velocity dispersion ( σ * ), abundance-matching halo mass ( M AM ), and satellite velocity dispersion ( σ s ), and their dependencies on galaxy and group properties. In general, these proxies all have strong positive correlations with M h , consistent with previous studies. We find that the M h – M * and M h – σ * relations depend strongly on group richness ( N sat ), while the M h – M AM and M h – σ s relations are independent of it. Moreover, the dependence on the star formation rate (SFR) is rather weak in the M h – σ * and M h – σ s relations, but very prominent in the other two. σ s is thus the best proxy among them, and its scaling relation is in good agreement with hydrodynamical simulations. However, estimating σ s accurately for individual groups/clusters is challenging because of interlopers and the requirement for sufficient satellites. We construct new proxies by combining M * , σ * , and M AM , and find that the proxy with 30% contribution from M AM and 70% from σ * can minimize the dependence on N sat and the SFR. We obtain the M h –supermassive black hole (SMBH) mass relation via the SMBH scaling relation and find indications for rapid and linear growth phases for the SMBH. We also find that correlations among M h , M * , and σ * change with M * , indicating that different processes drive the growth of galaxies and SMBHs at different stages.